Pelatihan Pemasaran Produk UMKM Hasil Olahan Anggur Laut di Paciran Lamongan - Ahmad shofiyuddin*; Nur Mahmudah; Moh. Mu’alliful Ilmi (Universitas Lancang Kuning, 2023)
One of the obstacles faced by Small and Medium Enterprises (SMEs) in Paciran is the skill constraint of using technology and marketing. Based on preliminary studies, SMEs in Paciran Village need business development through online platforms so that they can compete with new online businesses. The purpose of writing this article is to identify the use of SMEs marketing media in Paciran Village, and describe the marketing development efforts of SMEs in Paciran Village. The method of implementing this community service is service learning. The identification results of fifty-five coastal residents of Paciran Village showed that SMEs in Paciran Village used social media such as Facebook, WhatsApp, and Instagram (17.14%), then (4.32%) used the Shopee Application, while (78.54%) used traditional methods without utilizing technology such as selling at the market, and opening stands / shops at home. This activity has provided an understanding to SMEs in Paciran Village the importance of developing marketing through online platforms, as well as improving the skills of SMEs in Paciran Village using marketing processed sea grape products through online platforms.